Formula vitae honestae Marcina z Bragi i „zaginione” pismo Seneki De quattuor virtutibus - Wyszomirski, Sławomir (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
There are obvious similarities between the language of Formula vitae honestae by Martin of Braga and preserved letters of Lucius Annaeus Seneca. However, it cannot be proved, despite numerous speculations, that Formula vitae honestae is a summary or rather an extract of some non-preserved Seneca’s paper. The article emphasises the fact that there are not only language and stylistic similarities between these two writers but also there are similarities in the way of understanding and defining so called cardinal virtues, i.e. prudentia, fortitudo (magnanimitas – by Martin of Braga), temperantia (continentia – by Martin of Braga) and iustitia.
Formula vitae honestae by Martin of Braga and „lost” Seneca’s paper De quattuor virtutibus
The article “Formula vitae honestae” by Martin of Braga and “lost” Seneca’s paper “De quattuor virtutibus” emphasises that it is impossible to prove, despite numerous speculations, that Formula vitae honestae is the summary or the extract of some non-preserved Seneca’s paper, in particular De quattuor virtutibus which never existed. However, in spite of that, there are numerous language and stylistic similarities, discussed frequently in scientific literature, between Formula vitae honestae by Martin of Braga and preserved letters of Lucius Annaeus Seneca. The article discusses unquestionable similarities in the way of understanding and defining so called cardinal virtues, i.e. prudentia, fortitudo (magnanimitas – by Martin of Braga), temperantia (continentia – by Martin of Braga) and iustitia. They prove the dependence of Formula vitae honestae by Martin of Braga on the thought of Seneca the Younger.
Keywords: Martin of Braga; Formula vitae honestae; Lucius Annaeus Seneca; primae virtutes; prudentia; fortitudo; magnanimitas; temperantia; continentia; iustitia